A TEACHER'S MORAL AND ETHICAL STANDARDS ARE THE KEY TO HIS SUCCESS (Web of Teachers: Inderscience Research, 2025)
Activity known one field with practitioner to people relevant moral There are also norms and requirements. Such morality professional ethics It is called. Everyone in society dominant was morality with profession morality between known one attitude This is common. with privacy between is a relationship. Profession morality universal morality theory rules and disadvantages in itself embodies, clarifies and develops.